Vulnerability of Arctic Ocean microbial eukaryotes to sea ice loss - Jackson, VLN; Grevesse, T; Kilias, ES; Onda, DFL; Young, KF; Allen, MJ; Walsh, DA; Lovejoy, C; Monier, A (Nature Research, 2024)
The Arctic Ocean (AO) is changing at an unprecedented rate, with ongoing sea ice loss, warming and freshening impacting the extent and duration of primary productivity over summer months. Surface microbial eukaryotes are vulnerable to such changes, but basic knowledge of the spatial variability of surface communities is limited. Here, we sampled microbial eukaryotes in surface waters of the Beaufort Sea from four contrasting environments: the Canada Basin (open ocean), the Mackenzie Trough (river-influenced), the Nuvuk region (coastal) and the under-ice system of the Canada Basin. Microbial community structure and composition varied significantly among the systems, with the most phylogenetically diverse communities being found in the more coastal systems. Further analysis of environmental factors showed potential vulnerability to change in the most specialised community, which was found in the samples taken in water immediately beneath the sea ice, and where the community was distinguished by rare species. In the context of ongoing sea ice loss, specialised ice-associated microbial assemblages may transition towards more generalist assemblages, with implications for the eventual loss of biodiversity and associated ecosystem function in the Arctic Ocean.